Noroeste da África - Nordeste do Brasil (Província Borborema) ensaio comparativo e problemas de correlação - Neves, Benjamim B. Brito; Van Schmus, William R.; Fetter, Allen H. (Geologia USP. Série Científica, 2001)
The geological correlation between Northwest Africa and Northeast Brazil faces a series of problems of both virtual and real natures. The lack of an IGCP (International Geological Correlation Program) on this subject is a crucial aspect. The first group of problems encompasses the heterogeneity backgrounds of geological knowledge (much of which is in papers of restricted circulation) as well as the diversity of scientific thought in the schools involved with this problem. Recent improvements in pre-drift (Aptian) paleogeographic maps, and a series of new PhD theses on the Precambrian shield in Brazil and Africa have stimulated the authors to review this theme. The correlation between the large cratonic blocks that confine the Brasiliano-Pan-African System - São Luís- and West African cratons in the north and the São Francisco and Congo-Kasai-Angola cratons in the south - is relatively well assigned and reasonably constrained from the litho-stratigraphic and tectonic points of view. These crátons/blocks seem to have been major fragments of the same Mesoproterozoic supercontinent, in which Paleoproterozoic orogenic collage was very important. Similarly, the set of Neoproterozoic orogenic belts that delimitate external outlines of these cratonic nuclei presents only minor correlation problems for discussion, such as those to the north, as in the case of the Médio Coreaú/Dahomeyides-Pharusian belts, or those to the south, as in the case of Sergipano/Oubanguides-Lindian belts. The main problems concern the branching systems of orogens of the internal Brasiliano/Pan-African domains, distal to cratonic nuclei. North of the Patos (Patos-Garoua) shear zone in the northern part of the Borborema Province, a large basement block has been identified that contains several vestigial supracrustal belts ("schist belts"). It is considered a tectonic-stratigraphic terrane, former part of Rodinia (like the cratonic nuclei) and considerably reworked during Brasiliano - Pan African events. This reworked landmass mostly composed of high-grade rocks Paleoproterozoic (2.35, 2.15, 2.0 Ga), orthogneisses of varied compositions, with minor insertions of calc-silicatic and aluminous gneisses, extends castward from NW Ceará to the Brazilian continental margin and, in Africa, from the coast far into the interior of Niger. This terrane displays a complex structural framework (Transamazonian/Eburnian) involving some small Archean nuclei (3.45; 2.8 / 2.6 Ga). Several scattered schist belts overlying this basement block are composed of volcano-sedimentary sequences of Late Paleoproterozoic (Statherian) and Neoproterozoic (ca. 820 Ma, 730, 640-600 Ma) ages, all of them reworked during the last phases of the Brasiliano collage. Although the radiometric data for the schist belts of Nigeria are controversial, the recent set of Neoproterozoic data from Ceará and Rio Grande do Norte (Brazil) may be extended to Africa. In the central part of the Borborema Province, between the Patos (Patos- Garoua) and Pernambuco/Ngaounderé shear zone systems ("Median Shear Corridor") correlation is still a difficult. In the Brazilian territory an Early-Neoproterozoic (1000-960 Ma"Cariris Velhos") fold belt has been identified, which seems to be part of the worldwide framework of the Grenvillian collage. There is little evidence for this event on the African side, however. Additionally, correlation of Neoproterozoic fold belts well-exposed in Brazil is rather difficult due to the scattered record and deeper crustal nature of these supposed African equivalents.